Two Dimensions of Moral Cognition as Correlates of Different Forms of Participation in Bullying - Caravita, Simona C. S.; Finne, Johannes N.; Fandrem, Hildegunn (Frontiers in Psychology, 2022)
The present study investigated the extent to which moral disengagement and the tendency to consider moral rules as socio-conventional rules are distinct dimensions of morality, and their association with three different forms of participation in bullying (perpetrating bullying, defending the victim and passive bystander behavior). These two types of moral cognitions have been theorized in different models of morality and are usually studied independently, even if research on moral shifts (the interpretation of a moral rule transgression as a socio-conventional rule transgression) suggests some possible overlaps. A group of 276 Italian students from primary and middle school (aged 8–15) completed self-reports assessing moral disengagement, socio-conventional perception of moral rules, and participation in bullying as bully, defender of the victim and passive bystander. Results from structural equation modeling analysis confirmed that moral disengagement and socio-conventional comprehension of aggressions are separate and moderately connected morality dimensions. Controlling for age, gender and SES, only moral disengagement was positively associated with perpetrating bullying. These results point to moral disengagement as the critical component of moral cognitions to be addressed in interventions.